2007
DOI: 10.1002/jcb.21596
|View full text |Cite
|
Sign up to set email alerts
|

A new, unexpected action of olomoucine, a CDK inhibitor, on normal human cells: Up‐regulation of CLIMP‐63, a cytoskeleton‐linking membrane protein

Abstract: Inhibition of cyclin-dependent kinases (CDKs) is a novel strategy in the therapy of human malignancies. The pharmacological CDK inhibitors representing a few distinct classes of compounds exert different target specificity. Considering the fact that dividing and quiescent cells differ in their CDK activity and in the pattern of their expression, one might expect that anti-proliferative efficiency of the pharmacological CDK inhibitors would depend on the mitotic index of treated cells. The present article shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Its cell cycle inhibitory effect strongly differs between cancer and normal cells. Whereas the exponentially growing human MCF‐7 breast cancer cells, which show a high mitotic potential, are arrested in G 2 phase of the cell cycle, 6 ROSC has almost no effect on the cell cycle of normal MRC‐5 human embryo fibroblasts, 8 which have only a very low mitotic index. Moreover, ROSC has stronger antiproliferative action in MCF‐7 than in MRC‐5 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Its cell cycle inhibitory effect strongly differs between cancer and normal cells. Whereas the exponentially growing human MCF‐7 breast cancer cells, which show a high mitotic potential, are arrested in G 2 phase of the cell cycle, 6 ROSC has almost no effect on the cell cycle of normal MRC‐5 human embryo fibroblasts, 8 which have only a very low mitotic index. Moreover, ROSC has stronger antiproliferative action in MCF‐7 than in MRC‐5 cells.…”
Section: Introductionmentioning
confidence: 99%
“…OLO, a substituted purine analogue, is an approximately 10‐ to 20‐fold weaker CDK inhibitor than ROSC. OLO has almost no effect on the proliferation and cell cycle progression of human diploid MRC‐5 fibroblasts 23 but strongly affects the viability of human HL‐60 cancer cells. Because MRC‐5 cells exhibit a low mitotic index and the reduced ratio of S phase compared with HL‐60 cells, the question of what might determine the sensitivity of cells to OLO arose: primarily the proliferative status of the treated cells or perhaps other endogenous factors?…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that OLO did not affect the viability of normal human MRC‐5 fibroblasts, but it inhibited the proliferation of human HL‐60 leukemia cells. After exposure of HL‐60 cells to OLO at a final concentration of 150 μmol/L for 24 h, the number of living cells was markedly reduced 23 . However, the exact mechanism by which leukemic cells were eliminated has not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Olomoucine is also a 2,6,9-trisubstituted purine [1]. Olomoucine displays lower pharmacological potency than roscovitine but a similar, though not identical, activity profile [7]. Interestingly, olomoucine has an inactive isomer, named iso-olomoucine that becomes the ideal negative control for biological experiments [8,9].…”
Section: Introductionmentioning
confidence: 98%